Biosafety, Functionalities, and Applications of Biomedical Micro/nanomotors. Issue 24 (17th February 2021) - Wan, Mimi; Li, Ting; Chen, Huan; Mao, Chun; Shen, Jian
Abstract: Due to their unique ability to actively move, micro/nanomotors offer the possibility of breaking through the limitations of traditional passive drug delivery systems for the treatment of many diseases, and have attracted the increasing attention of researchers. However, at present, the realization of many advantages of micro/nanomotors in disease treatment in vivo is still in its infancy, because of the complexity and particularity of diseases in different parts of human body. In this Minireview, we first focus on the biosafety and functionality of micro/nanomotors as a biomedical treatment system. Then, we address the treatment difficulties of various diseases in vivo (such as ophthalmic disease, orthopedic disease, gastrointestinal disease, cardiovascular disease, and cancer), and then review the research progress of biomedical micro/nanomotors in the past 20 years, Finally, we propose the challenges in this field and possible future development directions Abstract : Research on micro/nanomotors has been booming in the past two decades, and their applications in the biomedical field have also received increasing attention. This Minireview summarizes research progress in the biosafety, functionality, and therapeutic effect of micro/nanomotors that can be used to treat different diseases. The direction of future developments is also discussed.